Expression Profiling of Proliferation and Apoptotic Markers along the Adenoma-Carcinoma Sequence in Familial Adenomatous Polyposis Patients. (13th February 2013) - Wang, Jayson; El-Masry, Nabil; Talbot, Ian; Tomlinson, Ian; Alison, Malcolm R.; El-Bahrawy, Mona
Abstract : Introduction . Familial adenomatous polyposis (FAP) patients have a germline mutation in the adenomatous polyposis coli ( APC ) gene. The APC protein interacts with beta-catenin, resulting in the activation of the Wnt signalling pathway. This results in alterations in cell proliferation and apoptosis. We investigated the expression of beta-catenin and related proliferation and apoptotic factors in FAP patients, exploring the expression along the adenoma-carcinoma sequence. Methods . The expression of beta-catenin, p53, bcl-2, cyclin-D1, caspase-3, CD10, and Ki-67 proteins was studied by immunohistochemistry in samples of colonic nonneoplastic mucosa (n = 71 ), adenomas (n = 152 ), and adenocarcinomas (n = 19 ) from each of the16 FAP patients. Results . The expression of beta-catenin, caspase-3, cyclin-D1, and Ki-67 was increased in both adenomas and carcinomas in FAP patients, compared with normal mucosa. p53 and CD10 expression was only slightly increased in adenomas, but more frequently expressed in carcinomas. Bcl-2 expression was increased in adenomas, but decreased in carcinomas. Conclusion . This is the first study investigating collectively the expression of these molecules together in nonneoplastic mucosa, adenomas, and carcinomas from FAP patients. We find that beta-catenin and related proliferative and apoptotic factors (cyclin-D1, bcl-2, caspase-3, and Ki-67) are expressed early in the sequence, in adenomas. However, p53 and CD10 are often expressed later in the sequence, in carcinomas.